A career preparation framework for learners with disabilities toward tertiary placement - Vidal, Lutze-Sol Aplaon (College of Education, University of the Philippines Diliman, 2019)
Learners with disabilities (LWD) experience difficulties which may persist throughout their lifespan. Like other individuals, LWD also face challenges as they prepare for their future. As such, important elements have to be considered in making decisions about and preparing for a career. For learners with disabilities (LWD), however, the disability itself becomes an important consideration before a placement decision is made. This research studied the career preparation of LWD, specifically, the elements that contributed to their decision to pursue tertiary placement as a career option. Using a sequential exploratory mixed method research design, quantitative and qualitative data was collected and analyzed. Quantitative data was gathered through a survey of 18 learners with autism, attention deficit disorder (ADD) and attention deficit/hyperactivity disorder (AD/HD) and 50 parents of learners with disabilities (PLWD). Qualitative data was gathered through interviews. The results generated through thematic analysis showed the following themes: a) assessment, b) intervention, c) academic placement, d) personal and family perceptions, and e) home and community resources as elements that LWD and PLWD considered in making career decisions. All data gathered was utilized to construct a framework that described factors considered in the career preparation of learners with disabilities.